2012
DOI: 10.1126/scisignal.2002274
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Signaling and AXIN1 Regulate Apoptosis Triggered by Inhibition of the Mutant Kinase BRAF V600E in Human Melanoma

Abstract: As the Wnt/β-catenin signaling pathway is linked to melanoma pathogenesis and to patient survival, we conducted a kinome siRNA screen in melanoma cells to expand our understanding of kinases that regulate this pathway, and to illuminate potential therapeutic directions. We found that BRAF signaling, which is constitutively activated in many melanomas by the BRAFV600E mutation, negatively regulates Wnt/β-catenin signaling in human melanoma cells. As inhibitors of BRAFV600E show promise in ongoing clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
164
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(179 citation statements)
references
References 52 publications
(93 reference statements)
12
164
1
2
Order By: Relevance
“…In addition, the percentage of apoptotic cells was significantly increased by overexpression of AXIN1. This result was in line with those of previous studies, which also suggested that AXIN1 could significantly induce cancer cell apoptosis (11,37). Next, the potential mechanism of AXIN1 overexpression-induced apoptosis was explored.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the percentage of apoptotic cells was significantly increased by overexpression of AXIN1. This result was in line with those of previous studies, which also suggested that AXIN1 could significantly induce cancer cell apoptosis (11,37). Next, the potential mechanism of AXIN1 overexpression-induced apoptosis was explored.…”
Section: Discussionsupporting
confidence: 90%
“…50 In contrast, activation of MAPK signaling downstream of oncogenic BRAF can inhibit β-catenin effects in melanoma. 51 Therefore, interactions between the two signaling cascades may be highly cell type-and context-specific. 52 To assess whether BRAF/MAPK activation may immediately alter transcription of β-catenin target genes during serrated tumor development, we analyzed FAC-sorted residual ISCs after shortterm induction of BRAF V600K by microarrays, but found no immediate changes in β-catenin target gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt3a, an important member of the Wnt family, can interact with cell membrane-associated proteins and induce the accumulation of β-catenin. Some experimental evidence shows that accumulation or overexpression of Wnt and/or β-catenin could induce apoptosis in melanoma and hepatocellular carcinoma cells (14)(15)(16). Cell apoptosis in the perihematomal region may be involved in the process of secondary injury (17,18).…”
Section: Discussionmentioning
confidence: 99%